THE RESULTS OF THE STUDY OF THE TYPES AND COMPOSITION OF FISH OF THE ZARAFSHAN RIVER MIDDLE COURSE AND THE OQDARYA RESERVOIR - Buvraev Nurali Ravshan ugli; Tolibova Munisa Jurabek qizi; Bolqiboyeva Mukhlisa Mansur qizi (Web of Journals Publishing, 2025)
The ichthyofauna of the Zarafshan River and its watersheds, including fish species, is of great importance in maintaining ecological balance. This work analyzes the composition and diversity of fish species in the middle reaches of the Zarafshan River and the Akdarya reservoir. By studying these species, new information is provided on the state of the fish ecosystem in the river and its biodiversity.